Corruption and electoral process in Nigeria: examining the 2015 general election - Sule, Babayo; Mat, Bakri; Mohammed Sani, Mohammed Azizuddin (Universiti Tun Hussein Onn Malaysia Publisher’s Office, 2018)
Corruption is one of the socioeconomic malaises that bedeviled the Nigerian State for many decades which virtually eroded all aspects of good governance and effective service delivery to the populace. It has affected democratic governance particularly electoral process with vote buying, bribing of electoral body officials and manipulation of the entire process. This paper investigated how corruption affected the process and outcome of the 2015 General Election. The methodology adopted is qualitative case study of data collection and analysis where some agencies and stakeholders that are related to the area of study were selected for interview including INEC, EFCC, politicians, party stakeholders, academicians and members of the general public through focus group discussion. The paper discovered that, the entire process of 2015 General Elections was affected by corruption and corrupt practices in terms of using public treasury for campaign activities by politicians from the two major parties; APC and PDP in their campaign and other electoral activities comprising of vote buying, excessive media campaign, spending above limit and bribing of INEC officials. The paper recommends that, for corruption to be eschewed in the electoral process, the INEC should be allowed a free hand in running the elections and the EFCC should be involved in screening contestants for political office and violaters of electoral laws should be banned from active politics permanently. The paper contributed to the existing knowledge by presenting an area that has not been given adequate attention particularly in the methodology of research of this nature.